Effect of vacuum pressure on ethanol fermentation - Nguyen, Viet D. (Animo Repository, 2009)
This study presents batch ethanol fermentation processes at various vacuum pressures. Glucose was used as substrate to anaerobically produce ethanol using baker's yeast at 47-760 mmHg and 33°C. The results indicated that the baker's yeast can survive and convert glucose to ethanol without oxygen/air supply while the carbon dioxide generated, can be trapped by liquid nitrogen, thus allowing vacuum pressure to be maintained without running vacuum pump continuously. The advantage of fermentation under vacuum pressure comes from the high ethanol concentration collected in the cold-trap while maintaining the productivity of fermentation processes in a range of 1.7 to 2.2 g/L/h. When increasing fermentation time, the productivity at low pressure was increased and higher than those at atmospheric pressure. A significant amount of ethanol outlet product was collected in the cold-trap. This ethanol concentration increased while increasing fermentation time and reached approximately 50% by weight at the end of fermentation period corresponding to system pressure of 47 mmHg. A kinetic model for ethanol fermentation under vacuum was developed to investigate the effect of vacuum pressure on the growth rate and production rate of the baker's yeast. This kinetic model and its set of rate equation parameters were developed and validated by experimental data of batch fermentation processes at atmospheric pressure. © 2009 Asian Network for Scientific Information.